PERBANDINGAN SISTEM INFORMASI AKADEMIK (Fokus Ekonomi, 2011)
Information technology (IT) can improve an organization's competitive advantage, so manyorganizations rely on IT, is no exception with the Christian University of Satya Wacana (UKSW).In carrying out its main activities, UKSW supported by the Information Systems Academic SatyaWacana (SIASAT). Internal control is required an information system in order to achieveorganizational goals. COBIT is the standard SI control of a general nature and can be acceptedand implemented by the organization. This study aims to compare the SI Academic Satya Wacanaby way of its internal control analysis using the COBIT framework. In this study, the domain ofdelivery and support (DS) is chosen for comparison is done at every level of IT processes COBIT.The study found that UKSW already have internal controls in every level of control process ITCOBIT DS domain, where the internal control provides assurance that the academic services suchas admissions, student registration, course registration, grades and graduation is based onstandard operating procedures (SOPs) that have been set.Key Word: Information system, internal control, COBIT framework